Immunotherapy in Pediatric Hematologic Malignant Neoplasms - Kyung Taek Hong (The Korean Society of Pediatric Hematology-Oncology, 2020)
Childhood acute leukemia has achieved tremendous treatment outcome improvement over the past several decades. Given that pediatric leukemia remains the most common type of childhood malignant tumors, there are still unmet needs in relapsed/refractory diseases. Moreover, reducing the toxic adverse effects of chemotherapy is another big challenge. Over the past decades, immunotherapy in pediatric leukemia has achieved significant improvement. This review will focus on the recent development and achievement of bi-specific T-cell engagers, antibody-drug conjugates, and chimeric antigen receptor T cell therapies in pediatric leukemia. Moreover, several prevalent obstacles in administering these treatments will also be discussed. Based on the characteristics of each treatment, a variety of clinical trials are currently underway. As a new treatment modality, immunotherapy should be optimally applied based on disease conditions.